INVESTIGATION OF OECD COUNTRIES WITH MULTI-DIMENSIONAL SCALING ANALYSIS IN TERMS OF TRAFFIC ACCIDENT INDICATORS - Özlem BEZEK GÜRE (International Journal of Health Services Research and Policy, 2020)
his study tries to compare similarities and differences in OECD countries in terms of traffic accidents utilizing Multidimensional Scale Analysis (MDS). In the study, MDS analysis was used utilizing basic indicators such as the number of injuries, deaths and the number of accidents resulting in material damage in the traffic accidents that happened in 2017. As a result of analysis, stress values and RSQ values turned out to be 0.0000 and 1.0000, respectively. That the stress value has resulted as zero shows that there is no inconsistency; and the fact that RSQ value has been found to be 1 indicates that the accuracy rate of this analysis is high and the values are in excellent coherence. According to results obtained from the analyses, it is seen that Malta and Liechtenstein, in particular, have appeared to be in a very different position from other countries when the counties are compared in terms of traffic accidents. In the second dimension, the countries do not have positive load over 1. However, Mexico, which has the value of 0.6378 the closest positive value to 1, can be considered as the most important parser for this dimension. When the matrix of the differences is examined; Turkey and Liechtenstein have seemed to be the two countries very different from each other. It poses great importance in terms of both for individual and public health that the necessary precautions be taken by evaluating our country, Turkey, and other countries to decrease traffic accidents taking places at the top of the list as the most important death causes. It is clear that traffic accidents, a global public health problem, have a great influence on individuals and communities and national economies. It is necessary that especially, the countries such as the US, Japan, India, Germany, Korea and Turkey which take place in high ranks in terms of traffic accident indicators should develop national and international projects in order to face to this problem coming together. In addition, in local basis, taking serious precautions (substructure services, increasing traffic fines and education etc.) will help reduce human and economic losses to the lowest levels.